Survey of knowledge, attitudes and practices of obstetricians and gynecologists about screening for Hepatitis B virus infection among pregnant women in Iran, in 2018 - Jahed Bozorgan, Tayyebeh; Fatemi, Alireza; Azimi, Fatemeh (Student Research in Translational Medicine, 2020)
Background: Various screening programs for all pregnant women are presented in the first pregnancy visit to reduce the vertical transmission of Hepatitis B virus (HBV) infection from mother to fetus during labor. Obstetricians and gynecologists are often referred to as a reliable source for health information for pregnant women. The present survey aimed to assess the knowledge, attitudes and practices (KAP) of obstetricians and gynecologists regarding screening for HBV infection among pregnant women in Iran, in 2018. Methods: This KAP study was performed in 200 obstetricians and gynecologists in Iran using the available sampling method. Data were collected using a researcher-made, valid and reliable questionnaire which contained 4 parts, including demographic data (3 questions), knowledge (20 questions), attitude (5 questions), and practice (8 questions). The level of knowledge and practice was evaluated using the Likert score, and attitude was defined as positive or negative. The relation between knowledge, attitude and practice, as well as their relationship with the work experience of obstetricians and gynecologists was evaluated. Results: The mean age of obstetricians and gynecologists was 38.9±3.7 years. The knowledge and practice of obstetricians and gynecologists about the screening for HBV in pregnant women was good, and they had a positive attitude on this. There was a direct and significant relationship between knowledge, attitude and practice with each other, as well as between knowledge and lower work experience (P <0.05). Conclusion: Obstetricians and gynecologists play an important and strategic role in the creation and transfer of health information, and the development of preventative measures and control of HBV for pregnant women. Despite the knowledge and attitude of obstetricians and gynecologists being reported at an appropriate level, the moderate level of practice can be alarming.